The Effect of Cyanosis on Active Clotting Time During Diagnostic Catheterization - Akbar Molaei; Majid Malaki; Shahram Sadegvand (Journal of Cardiovascular and Thoracic Research, 2012)
Introduction: Cardiac catheterization is a common procedure which needs a careful coagulation monitoring. In our study, we aimed to find factors influencing active clotting time (ACT) following heparin therapy. Methods: ACT of 71 patients who were scheduled to undergo transcutaneous diagnostic catheterization and angiography were measured at baseline, 2 and 60 minutes after 50 IU/kg heparin loading. ACT in two groups of patients (cyanotic and non-cyanotic) was compared. All data were analyzed with Wilcoxon, Mann-Whitney test and Pearson in SPSS 16, P value less than 0.05 was considered significant. Results: ACT following heparin at 2nd and 60th minutes was not significantly different in cyanotic and non-cyanotic groups. At 60th minute following heparin administration, ACT decreased more dramatically in older children. Conclusion: Cyanosis does not affect ACT measures following heparin treatment. Moreover, after 60 minutes, heparin efficacy (ACT values) decreased more with increase in patients’ age.